2022
DOI: 10.1128/spectrum.00657-22
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Consortia and Their Metabolites Ameliorate the Symptoms of Inflammatory Bowel Diseases in a Colitis Mouse Model

Abstract: IBD is a chronic nonspecific inflammatory disease. IBD is characterized by a wide range of lesions, often involving the entire colon, and is characterized mainly by ulcers and erosions of the colonic mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 76 publications
(81 reference statements)
0
22
0
Order By: Relevance
“…Probiotics and probiotic consortia including Lactobacillus, Bacillus, Bifidobacterium, Clostridium, Enterococcus, Leuconostoc, Escherichia, and/or others could ameliorate the symptoms of the patients and mouse model of IBD, a recurrent disease that is difficult to cure, harbors the increased incidence at an accelerated rate, increases the disease burden, and impairs the quality of life. [32][33][34][35][36][37][38][39][40][41][42][43] Water kefir, a traditional fermented beverage, contained several bacteria including lactic acid bacteria (such as Lactobacillus, Leuconostoc, Bifidobacteria, Oenococcus, Pediococcus, and Lactococcus), acetic acid bacteria (such as Acetobacter, Gluconobacter, and Gluconacetobacter) and other bacteria (such as Zymomonas), as well as yeast including Saccharomyces, Dekkera, Zygotorulaspora, Hanseniaspora, Torulaspora, Kazachstania, Pichia, Kluyveromyces, and Yarrowia, which differed from the geographical origin of the water kefir grains and the fermentation substrates and conditions. 18,24,26 It has been reported that water kefir and/or its extraction exhibited antimicrobial activity, anti-inflammatory properties, antioxidant activity, and so on, 18,24,26 but their effects on the symptoms of IBD were little known.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics and probiotic consortia including Lactobacillus, Bacillus, Bifidobacterium, Clostridium, Enterococcus, Leuconostoc, Escherichia, and/or others could ameliorate the symptoms of the patients and mouse model of IBD, a recurrent disease that is difficult to cure, harbors the increased incidence at an accelerated rate, increases the disease burden, and impairs the quality of life. [32][33][34][35][36][37][38][39][40][41][42][43] Water kefir, a traditional fermented beverage, contained several bacteria including lactic acid bacteria (such as Lactobacillus, Leuconostoc, Bifidobacteria, Oenococcus, Pediococcus, and Lactococcus), acetic acid bacteria (such as Acetobacter, Gluconobacter, and Gluconacetobacter) and other bacteria (such as Zymomonas), as well as yeast including Saccharomyces, Dekkera, Zygotorulaspora, Hanseniaspora, Torulaspora, Kazachstania, Pichia, Kluyveromyces, and Yarrowia, which differed from the geographical origin of the water kefir grains and the fermentation substrates and conditions. 18,24,26 It has been reported that water kefir and/or its extraction exhibited antimicrobial activity, anti-inflammatory properties, antioxidant activity, and so on, 18,24,26 but their effects on the symptoms of IBD were little known.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics, live microorganisms that confer health benefits to the host, have been reported to have many functions, such as ameliorating inflammatory bowel diseases and improving obesity. 33,38 Our previous studies have demonstrated that L. plantarum CCFM8610 has many probiotic functions, such as alleviating enteric diseases, preventing gut microbiota dysbiosis, and protecting the gut barrier from toxins. 5,[12][13][14]39 In addition, this strain is beneficial for host health because it produces beneficial metabolites and modulates immune reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found a significant increase in the abundance of Rikenellaceae , despite a decrease in that of Bacteroidetes. It is widely recognized that Lactobacillus and Bifidobacterium could regulate intestinal metabolites, reduce inflammation, and improve immunity [ 13 , 60 ]. Additionally, it was important that members of Clostridiaceae are known for the production of butyrate by carbohydrate fermentation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%